New Ways of Working in UK mental health services: developing distributed responsibility in community mental health teams?. (3rd March 2016) - Procter, Stephen; Harrison, Deborah; Pearson, Pauline; Dickinson, Claire; Lombardo, Chiara
Abstract: Background : This paper examines the introduction and operation of a number of support roles in mental health services. This is done in the context of concerns about the effectiveness of CMHTs. Aims : Three questions are addressed: the degree to which concern for the work of consultant psychiatrists informed the introduction of the new roles; what the reforms implied for the work of the psychiatrist and those in new roles; and the impact of any changes on the operation of CMHTs. Method : Data were collected as part of a national-level evaluation. The main means of collection was the semi-structured interview. Results : The study shows: that reform was underpinned by concerns about the workload of psychiatrists; and that while in principle the responsibilities of the psychiatrist were to be distributed across other team members, those in new roles felt themselves to be isolated. Conclusions : Despite the intentions of policy, the creation of the new roles did little to extend the idea of distributed responsibility in CMHTs.